Treatment and outcome patterns in European patients with Waldenström's macroglobulinaemia: a large, observational, retrospective chart review. Issue 7 (July 2018) - Buske, Christian; Sadullah, Shalal; Kastritis, Efstathios; Tedeschi, Alessandra; García-Sanz, Ramón; Bolkun, Lukasz; Leleu, Xavier; Willenbacher, Wolfgang; Hájek, Roman; Minnema, Monique C; Cheng, Mei; Bilotti, Elizabeth; et al.
Summary: Background: Treatment options for Waldenström's macroglobulinaemia are heterogeneous, and no well established treatment standards exist. Although guidelines from the Eighth International Workshop on Waldenstrom's Macroglobulinemia were published in 2016, inconsistent awareness and budget constraints have prevented their widespread implementation, and real-life treatment patterns might differ across health-care systems. We aimed to generate information about treatment and outcome patterns for patients with Waldenström's macroglobulinaemia outside of clinical trials. Methods: In this large, observational, retrospective chart review, academic and community physicians in ten European countries were invited to retrospectively complete electronic records for patients with symptomatic Waldenström's macroglobulinaemia who had begun treatment after Jan 1, 2000, and before Jan 1, 2014, and had available clinical and biological data. The primary endpoints were reasons for treatment initiation, treatment choices, progression-free survival, and overall survival. We assessed the variables that affected choice of front-line therapy, progression-free survival, and overall survival in multivariate analyses. Findings: Electronic records were reviewed for 454 eligible patients. The most frequent reasons for starting front-line treatment were anaemia (in 328 [72%] patients) and constitutional symptoms (in 264 [58%] patients). Choice of therapy varied between front-line, second-line, and third-line approaches; age; and type of institution. In the front-line setting, 193 (43%) of 454 patients received monotherapy, 164 (36%) received chemoimmunotherapy, and 95 (21%) received other combination regimens (data on front-line treatment were missing for one patient, and another patient received only steroids). After front-line treatment, median progression-free survival was 29 months (95% CI 25–31), median overall survival was not reached (not reached–not reached), and 10-year overall survival was 69% (62–74). In multivariate analyses, patients who were high risk according to the International Prognostic Scoring System for Waldenström Macroglobulinemia had significantly worse progression-free survival and overall survival than did those who were low risk. Additionally, progression-free survival was shortened in patients treated with monotherapy compared with those treated with chemoimmunotherapy or other combination therapies and in those treated at an academic institution compared with those treated in the community. Constitutional symptoms (excluding fatigue) were associated with worsened overall survival. Interpretation: This large observational dataset should inform and help set guidelines, and improve understanding of treatment practices and outcomes, for European patients with Waldenström's macroglobulinaemia. Funding: Pharmacyclics LLC (an AbbVie company).